2021
DOI: 10.3389/fpsyt.2021.737890
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rapid Interactive Screening Test for Autism in Toddlers Using Autism Diagnostic Observation Schedule™ Second Edition in Children at High-Risk for Autism Spectrum Disorder

Abstract: The Rapid Interactive screening Test for Autism in Toddlers (RITA-T) is a fast and inexpensive early screening measure for autism spectrum disorder (ASD) that was tested previously in children 18–36 months-old; the current validation study compared the RITA-T with the Autism Diagnostic Observation Schedule™ Second Edition (ADOS-2). The hypothesis is to validate the RITA-T with comparison to the ADOS-2. Thirty-five individuals (18–84 months-old) identified as at risk for ASD received the RITA-T and the ADOS-2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Given that positive screens have previously been associated with 2-year and now with 3-year developmental delays, as well as more concerning autism-related scores on the CBCL PDD scale, it may be pertinent to pair the 2-stage parent-report autism risk screening tool with additional screening measures that more specifically target autism symptoms (eg, the Rapid Interactive Screening Test for Autism in Toddlers [RITA-T]) or to assess information from longitudinal screening and assessment combinations to understand which children need to be seen more quickly for continued autism-specific assessment. Research suggests that a 2-level screening process may produce the most accurate autism screening outcomes by providing strong distinctions between autism and other developmental concerns .…”
Section: Discussionmentioning
confidence: 99%
“…Given that positive screens have previously been associated with 2-year and now with 3-year developmental delays, as well as more concerning autism-related scores on the CBCL PDD scale, it may be pertinent to pair the 2-stage parent-report autism risk screening tool with additional screening measures that more specifically target autism symptoms (eg, the Rapid Interactive Screening Test for Autism in Toddlers [RITA-T]) or to assess information from longitudinal screening and assessment combinations to understand which children need to be seen more quickly for continued autism-specific assessment. Research suggests that a 2-level screening process may produce the most accurate autism screening outcomes by providing strong distinctions between autism and other developmental concerns .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing the Autism Diagnostic Observation Scale module 2 (ADOS-2) and RITA-T found a high level of similarity between the two tests in terms of distinguishing ASD (Kong et al, 2021). We found a significant correlation between the RITA-T total scores and the CARS total scores in both the whole group and the ASD group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, translation and validation of the instrument is under way in a range of other countries and cultures. 14 , 15…”
Section: Methodsmentioning
confidence: 99%
“…In addition, translation and validation of the instrument is under way in a range of other countries and cultures. 14,15 This model strongly relies on the network that it builds around EI providers, PCP, and ASD diagnosticians. Furthermore, it encourages increased collaboration between PCP and EI providers, and diagnosticians.…”
Section: Rita-t and Rita-t Screening Modelmentioning
confidence: 99%